Bicultivo de rúcula e alface em policultivo com cenoura sob quantidades de flor-de-seda e proporções de densidades populacionais - Oliveira, Lenilton Alex de Araújo (2014)
This work was conducted in the period from August to December 2012 at the Experimental Farm Rafael Fernandes of the Federal Rural University of Semi-Arid, Mossoró - RN, with the aim of studying the agroeconomic viability of the bicropping of arugula and lettuce intercropped with carrot in function of different amounts of roostertree incorporated into the soil and the proportions of population densities among the component crops in the semiarid conditions of the State of Rio Grande do Norte. The experimental design was a randomized complete blocks with four replications with treatments arranged in a 4 x 4 factorial scheme. The first factor was composed of the amounts of roostertree incorporated into the soil (10.0, 25, 40 and 55 t ha-1 on a dry basis) and the second factor by the proportions of population densities of the components crops in the polyculture 50R-50C-50A%; 40R-50C-40A%; 30R-50C-30A% and 20R-50C-20A% of populations recommended in the sole crops (PRSC) of: 1.000.000 plants per hectare for arugula, 500.000 plants per hectare for carrot and 250.000 plants per hectare for lettuce. The characteristics evaluated in crops were: plant height, number of leaves per plant, diameter of the lettuce plants, dry and green mass of shoots, total and commercial productivity of the roots, root dry mass and classified productivity of carrot roots. The indices of agronomic/biological efficiency evaluated were: partial land equivalent ratios of crops and of the polyculture. Economic indicators of gross income, net income, rate of return, profit margin and modified monetary advantage and yield efficiency index for DEA were also evaluated. The major agronomic polyculture indexes were obtained when the system was fertilized with the amount of 55 t ha-1 roostertree biomass. The population proportion that resulted in these higher indices was the 50R-50C-50A (%) of the recommended in the sole crops. The economic index that provided better efficiency of polyculture was that obtained with the profit margin of 37.23% in the optimum dosage of 24.25 t ha-1 of roostertree added to the soil. The highest proportions of population densities had an important role in obtaining of these indices. The use of roostertree as green manure proved viable in the polyculture of arugula, carrot and lettuce